Changes in Immune Markers for Prostate Cancer Patients Pre and Postoperation - Abbas, Maysoon (Iraqi Journal of Science, 2023)
This study includes 15 male healthy and 30 male patients diagnosed with prostatecancer inciude (18 cases in stages I & II and 12 cases in III – stage). All the patientswere suffered from urinary tract infection ( UTI) . The mean age is (57.33± 5.02)years range ( 45-63) years, as cases and controls Patients with prostate cancer weretreated admits an Educational Baghdad Hospital, and Central Public HealthLaboratory and Radiation and Nuclear Medicine Hospital in Baghdad, duringperiod 1/6/2008 to 1/12/2010 are included in this study. The markers Prostatespecificantigen (CA PSA), Interleukins ( IL -1 , IL-2, IL-3, IL-5) andImmunoglobulins ( IgG, IgM, IgE) are estimated by using ELISA method. TheClean-Catch midstream urine of the patients were collected, and cultured on bloodagar and MacConky agar to isolation of the pathogenic bacteria causes andassociated with prostate cancer. The isolated bacteria were identified according tomorphological and using biochemical tests.The aim of this study is to fined out changes in some immune markers in prostatecancer patients and if any correlation exists between the tumor marker in patientsserum pre and post-operation, and the bacterial pathogens of the UTI and itscorrelation with prostate cancer risk.The results show , a significant difference in CAPSA levels between healthycontrol and prostate cancer patients ( stages I , II , III ) pre-operation ( P> 0.05 ),while no appear significant difference between healthy and patients post-operation ,The comparison between prostate cancer pre and post-operation was showed asignificant difference ( t=7.042,P > 0.05 ) with positive correlation. However ,statistical analysis shows a significant difference in interleukins ( IL–1 , IL–2 , IL-3 , IL-5 ) between healthy and prostate cancer patients pre-operation, whereas nosignificant difference between them in post-operation , only IL-5 , also is increasedsignificantly (P<0.05 ) and positive correlations in interleukins levels at prostatecancer patients pre and post-operation. The results show a significant difference inimmunoglobulins (IgG, IgE, IgM ) between healthy control compared with prostatecancer patients pre-operation, but no significant difference post-operation. Bycomparing between prostate cancer pre and post-operation a significantcorrelation(P>0.05) but only IgM has no correlation( r=0.149,P=0. 432) wereappeared.In this study 30(100%) patients are shown to be urine culture positive. Wereinciude E. coli with frequency rate of 43.33%, Pseudomonas aerginosa (16.66 %),Klebsiella spp. (16.66%), Enterobacter spp. (10 %), , Acinetobacter spp. (3.33%),Serratia spp. (3.33%), and Staphylococci spp. (6.66%).